2020
DOI: 10.1016/j.arabjc.2020.09.037
|View full text |Cite
|
Sign up to set email alerts
|

TAT-peptide conjugated repurposing drug against SARS-CoV-2 main protease (3CLpro): Potential therapeutic intervention to combat COVID-19

Abstract: The Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that originated in Chinese city of Wuhan has caused around 906,092 deaths and 28,040,853 confirmed cases worldwide (WHO, 11 September, 2020). In a life-threatening situation, where there is no specific and licensed anti-COVID-19 vaccine or medicine available; the repurposed drug might act as a silver bullet. Currently, more than 211 vaccines, 80 antibodies, 31 antiviral drugs, 35 cell-based, 6 RNA-based and 131 other drugs are in clinical trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Another study has also found that α-helical peptides block ACE2, leading to the inhibition of SARS-CoV-2 [ 35 ]. In another in-silico study, the efficacies of lopinavir, ritonavir, hydroxychloroquine, and favipiravir drugs were improved by adding TAT-peptide to them, and their interactions with 3CL have considerably increased [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study has also found that α-helical peptides block ACE2, leading to the inhibition of SARS-CoV-2 [ 35 ]. In another in-silico study, the efficacies of lopinavir, ritonavir, hydroxychloroquine, and favipiravir drugs were improved by adding TAT-peptide to them, and their interactions with 3CL have considerably increased [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, significant resources of the scientific community are involved in the search for effective methods of treating coronavirus infection. Many strategies have been proposed, among which peptides play an important role [ 17 ]. Interestingly, a similar target effect is a characteristic of AMPs with lectin-like functions (e.g., defensins [ 18 ] and hevein-like peptides [ 19 ], which can bind to N-glycosylated sites of the viral spike protein or the receptor, which ultimately prevents penetration of the virus into the host cell [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review is based on the treatments given in the case of SARS-CoV and MERS, which could also be effective against SARS-CoV-2 since SARS-CoV-2 is closely related to SARS-CoV and have 80% sequence identical [ 8 ]. Plants are a good source of natural medication and an alternative to antibiotic treatment because the excessive use of antibiotics is responsible for drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 genome is 80% similar to the previous human coronavirus SARS-CoV [ 8 ]. For some of the encoded proteins such as coronavirus main proteinase (3CLpro), papain-like protease (PLpro), and RNA-dependent RNA polymerase (RdRp) the sequence similarity is very high (96%) between SARS-CoV, and SARS-CoV-2 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%